Incorporating pharmacodynamic considerations into caffeine therapeutic drug monitoring in preterm neonates. Issue 1 (December 2016) - Yu, Tian; Balch, Alfred; Ward, Robert; Korgenski, E.; Sherwin, Catherine
Abstract Background This study sought to assess the pharmacokinetic and pharmacodynamic relationships of caffeine citrate therapy in preterm neonates who had therapeutic drug monitoring (TDM) in the post-extubation period. Methods A retrospective observational study was conducted in preterm neonates who received caffeine citrate therapy for apnea of prematurity and had TDM done in the post-extubation period between January 2006 and October 2011. The relationships between pharmacodynamic effects (heart rate, respiratory rate, episodes of apnea, adverse events) and caffeine serum concentrations were explored. Results A total of 177 blood samples were obtained from 115 preterm neonates with a median (range) gestational age of 29 (24 – 33) weeks and birth weight of 1230 (607 – 2304) kg. Caffeine citrate therapy was initiated at a median (interquartile range) postnatal age of 1 (1 – 3) day and TDM was performed at a postnatal age of 15 (10 – 24) days. No direct correlations were found between respiratory rate or apneic episodes and caffeine serum concentrations; however, heart rate and caffeine serum concentrations were significantly correlated (p < 0.05). Dosing regimen of 40/5 mg/kg q12h (loading dose/maintenance dose, time interval) led to similar endotracheal re-intubation rate but increased percentage of patients experiencing tachycardia compared to the standard regimen of 20/5 mg/kg q24h (44.7 % vs 10.2 %, p < 0.001). Conclusion Based on this retrospective study, no correlation between episodes of apnea and caffeine serum concentrations was found in neonates who had TDM of caffeine citrate therapy in the post-extubation period, whereas a significant association between tachycardia and concentrations existed. Notwithstanding the absence of severe adverse reactions, TDM should be considered in critically ill neonates with unexplained adverse effects, such as tachycardia.